Fatigue Increases ACL Injury Risk in Youth Athletes: Risk Assessment Study Using Drop-jump Test. Issue 7 (30th July 2018) - Fidai, Mohsin S.; Okoroha, Kelechi; Meldau, Jason E.; Borowsky, Peter A.; Meta, Fabien; Lizzio, Vincent A.; Redler, Lauren H.; Moutzouros, Vasilios; Makhni, Eric C.
Objectives: The impact of fatigue on injury risk to the anterior cruciate ligament (ACL) in adolescent athletes is unknown. Identifying athletes who demonstrate increased risk for injury may help determine who would benefit from early neuromuscular control intervention for injury prevention. The goal of this study was to determine if fatigue increases ACL injury risk in adolescent athletes using the drop-jump test to assess dynamic valgus. Methods: Youth and adolescent competitive athletes were recruited for this video analysis study. Participants were recorded performing the standard drop-jump test assessing dynamic valgus on landing three times. They then completed a standardized fatigue protocol consisting of a timed period of high-intensity aerobic tasks. A set amount of fatigue was quantified and achieved using a maximum vertical jump, which was compared to pre-fatigue values. The drop-jump test was then repeated three additional times post-fatigue. All drop-jump recordings (six in total) were randomized by order and scored for dynamic knee valgus by three independent reviewers. A multivariable analysis was performed to assess the correlation between demographic variables and injury risk. Results: Forty-seven female patients and thirty-eight male athletes were included in the study. The average age was 15.4 years (age 14-18). Athletes were found to have significantly higher ACL injury risk post-fatigue when compared to pre-fatigue (p = .001). Thirty-five athletes were found to change from low/medium injury risk pre-fatigue to medium/high risk post fatigue. No demographic variables were found to contribute to ACL injury risk. Conclusion: In adolescent athletes, fatigue appears to increase risk of ACL injury through drop-jump testing. Age, BMI, and hip width were not found to contribute to ACL injury risk. Implementation of neuromuscular or conditioning programs for at-risk athletes may reduce injury risk.